1997
DOI: 10.1103/physreve.56.2407
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium phase transition in the kinetic Ising model: Critical slowing down and the specific-heat singularity

Abstract: The nonequilibrium dynamic phase transition, in the kinetic Ising model in presence of an oscillating magnetic field, has been studied both by Monte Carlo simulation and by solving numerically the mean field dynamic equation of motion for the average magnetisation. In both the cases, the Debye 'relaxation' behaviour of the dynamic order parameter has been observed and the 'relaxation time' is found to diverge near the dynamic transition point. The Debye relaxation of the dynamic order parameter and the power l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 10 publications
0
82
1
Order By: Relevance
“…This behavior suggests that for low values of k, the system has a dynamic phase transition (DPT) between a high CO 2 productive dynamic phase and a nonproductive one. This is reminiscent of the behavior of ferromagnetic Ising or anisotropic XY or Heisenberg spin systems driven by a periodically oscillating field [18,19,20,21,22,23,24,25,26,27,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…This behavior suggests that for low values of k, the system has a dynamic phase transition (DPT) between a high CO 2 productive dynamic phase and a nonproductive one. This is reminiscent of the behavior of ferromagnetic Ising or anisotropic XY or Heisenberg spin systems driven by a periodically oscillating field [18,19,20,21,22,23,24,25,26,27,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…It was then studied further, both in mean-field models [3,4,5,6] and in kinetic Monte Carlo (KMC) simulations [5,6,7,8,9,10]. A review of this early work can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The nonequilibrium dynamic phase transition and the hysteretic response are the main characteristic features of the ferromagnetic system driven by time dependent magnetic field. Some observations or studies regarding -(i) divergences of dynamic specific heat and relaxation time near transition point [3,4], (ii) divergence of the relevant length scale near transition point [5], (iii) studies regarding existence of tricritical point [6,7], (iv) its relation with stochastic resonance [6], and the hysteresis loss [8] etc., establish that the dynamic phase transition is similar in many aspects to the well known equilibrium thermodynamic phase transition. This fact is further supported by some experimental findings like-(i) detection of dynamic phase transition in the ultra-thin Co film on Cu(001) system by surface magneto-optic Kerr effect [9,10], (ii) direct excitation of propagating spin waves by focussed ultra short optical pulse [11], (iii) the transient behaviour of dynamically ordered phase in uniaxial cobalt film [12] etc.…”
Section: Introductionmentioning
confidence: 99%